Market forces, trade union action, and the Phillips curve in Italy - F. MODIGLIANI; E. TARANTELLI (PSL Quarterly Review, 2013)
This study is an extension of two previous studies in which the authors build upon their model of trade union action on contract renewals. To this end, a distinction is made between the percentage of workers at any given moment of time whose new contracts take effect on or before the expiration date of their previous contract. The model is subjected to economic tests with data referring to the Italian industrial sector. The central conclusion is that, since with the wave of strikes initiated by the contract renewals of Fall 1969, the Phillips curve has shifted to the right and upwards and its slope for any given level of unemployment is nearly doubled with respect to the slope prevailing in the previous twenty years. Some implications concerning the present conditions of dynamic instability of the inflationary process are then highlighted.